Conflict and Global Security: An Integrated Approach to Addressing The Impact of Violations of Humanitarian Law - Humaidi Syarif Romas; Mario Christian Noya; Tarsisius Susilo; Sarwo Supriyo; Thomas HK. Sinaga (Interdisciplinary Social Studies, 2025)
Conflicts that take place in various regions of the world have a wide impact on global security, especially in terms of terrorism and mass migration. Violations of humanitarian law that occur in these conflicts often exacerbate the situation, with long-lasting implications for regional and international stability. This article aims to analyze how conflict-areas contribute to these global security problems, as well as how violations of humanitarian law can exacerbate humanitarian and political crises. Focusing on the interconnectedness between conflict, humanitarian law, and global security, this article emphasizes the need for a more integrated and holistic approach to maintaining and maintaining global security stability in the era of globalization. The findings of this article are expected to provide useful insights for policymakers in formulating more effective security strategies at the international level.